If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -21 = 5x Reorder the terms: -21 + 12x = 5x Solving -21 + 12x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -21 + 12x + -5x = 5x + -5x Combine like terms: 12x + -5x = 7x -21 + 7x = 5x + -5x Combine like terms: 5x + -5x = 0 -21 + 7x = 0 Add '21' to each side of the equation. -21 + 21 + 7x = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 7x = 0 + 21 7x = 0 + 21 Combine like terms: 0 + 21 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| c^2+9c+8=0 | | 2x^4-5x^3-8x^2-5x+2=0 | | 35x^3-28x^2+15x-12=0 | | 3y=7x+5 | | r^2-8tw+4rw-2t=0 | | 8y=4x-12 | | 118-5x=40x+18 | | 2y=-5x-4 | | 9-10x=40-17x | | 1-2u-8u^2=0 | | f(-2)=-x^3-11x^2-3x+2 | | G=FN | | 4x^2=16x^2 | | 5x+5=-99-8x | | 8x^2=16x^2 | | -63x^7-7x^6=0 | | -64-2x=8-10x | | 87-3x=9x+15 | | 16(x-3)=-33 | | 4(3x-9)=2(6x+2) | | 4y+5=50-5y | | 6+5x=50+x | | 2x+12=27-3x | | 6+3p-5=9p+-5p | | 49x^4+46x^2-3=0 | | 2x+5y+3yi+15-3i=0 | | 12-7p=82 | | 23456x-4456-47=45677 | | y=14-2x | | (3+i)(3-i)(2+6i)= | | (5+i)(5-i)(6+2i)= | | 5-6n=23 |